Lipid-based nanosystem of edaravone: development, optimization, characterization and in vitro/in vivo evaluation - Ankit Parikh; Krishna Kathawala; Chun Chuan Tan; Sanjay Garg; Xin-Fu Zhou (Taylor & Francis Group, 2017)
Edaravone (EDR) is a well-recognized lipophilic free radical scavenger for diseases including neurodegenerative disease, cardiovascular disease, and cancer. However, its oral use is restricted due to poor oral bioavailability (BA). The aim of present research was to enable its oral use by developing a lipid-based nanosystem (LNS). The components of LNS including oil, surfactants, and co-surfactants were selected based on their potential to maximize the solubilization in gastrointestinal (GI) fluids, reduce its glucuronidation and improve transmembrane permeability. The liquid LNS (L-LNS) with Capryol™ PGMC (Oil), Cremophor® RH 40:Labrasol®:TPGS 1000 (1:0.8:0.2) (Surfactant) and Transcutol P® (Co-surfactant) were optimized to form microemulsion having droplet size (16.25 nm), polydispersity index (0.039), % Transmittance (99.85%), and self-emulsification time (32 s). It significantly improved the EDR loading as well as its metabolism and permeability profile during transport across the GI tract. To overcome the possible drawbacks of L-LNS, Aerosil® 200 was used to formulate solid LNS (S-LNS), and its concentration was optimized based on flow properties. S-LNS possessed all quality attributes of L-LNS confirmed by solid-state characterization, reconstitution ability, and stability study. The dissolution rate of EDR was significantly enhanced with L-LNS and S-LNS in simulated gastric, and intestinal fluids. The pharmacokinetic study revealed significant improvement in relative BA, Cmax, and t1/2 with L-LNS and S-LNS against EDR suspension. Moreover, S-LNS showed superior cellular uptake and neuroprotective effect compared to EDR in SH-SY5Y695 cell line. An appropriate selection of the components of LNS could enable effective oral delivery of challenging therapeutics that are conventionally used by the parenteral administration.